2020
DOI: 10.3389/feart.2020.559430
|View full text |Cite
|
Sign up to set email alerts
|

Latest Permian Peltasperm Plant From Southwest China and Its Paleoenvironmental Implications

Abstract: A monospecific flora containing a peltasperm species, Germaropteris martinsii, is discovered from the uppermost Permian Kayitou Formation of Southwest China. The epidermal characteristics of G. martinsii from the South China Block are described for the first time on the basis of charcoalified specimens. The plant is characterized by small, leathery foliage with prominent papillate epidermal cells, and slightly sunken stomata. The stomatal apertures are covered by the long papillae of the surrounding subsidiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 75 publications
(106 reference statements)
1
9
0
Order By: Relevance
“…On the contrary, Ro mean (1.509%) and Ro max (2.670%) from 8.8 m indicate the charcoals were formed at a lower fire temperature during brief surface fires. This phenomenon is consistent with the turnover of vegetation from rainforest to herblands in the lower Kayitou Formation (Feng et al, 2020a, b).…”
Section: The Turnover Of Vegetationsupporting
confidence: 87%
See 4 more Smart Citations
“…On the contrary, Ro mean (1.509%) and Ro max (2.670%) from 8.8 m indicate the charcoals were formed at a lower fire temperature during brief surface fires. This phenomenon is consistent with the turnover of vegetation from rainforest to herblands in the lower Kayitou Formation (Feng et al, 2020a, b).…”
Section: The Turnover Of Vegetationsupporting
confidence: 87%
“…Fossil charcoals in sediments, as well as inertinite in coal beds, are widely accepted as a key index of palaeo-wildfires in deep time (Scott, 1989, Scott, 2000Scott and Glasspool, 2007). Wang (2015) and Yan et al (2019) have reported that the inertinite (Shen et al, 2011;Zhang et al, 2016;Feng et al, 2020a). In this study, we report more than 50 horizons in the Lengqinggou section containing charcoal fragments from the upper Xuanwei and the Kayitou formations, indicating that palaeo-wildfires are common and frequent phenomena during the latest Permian in Southwest China.…”
Section: Wildfire Implicationsmentioning
confidence: 99%
See 3 more Smart Citations